The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4097/kjae.2017.70.5.550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative incentive spirometry on fentanyl-induced cough: a prospective, randomized, controlled study

Abstract: BackgroundFentanyl-induced cough (FIC) has a reported incidence of 13–65% on induction of anesthesia. Incentive spirometry (IS) creates forceful inspiration, while stretching pulmonary receptors. We postulated that spirometry just before the fentanyl (F) bolus would decrease the incidence and severity of FIC.MethodsThis study enrolled 200 patients aged 18–60 years and with American Society of Anesthesiologists status I or II. The patients were allocated to two groups of 100 patients each depending on whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Preoperative incentive spirometry has an important role in anesthesia practice, improving pulmonary function in patients with chronic obstructive and restrictive lung diseases and preventing postoperative atelectasis. Goyal et al (2017) found that preoperative incentive spirometry before giving fentanyl would suppress FIC, along with the secondary benefit of preventing postoperative pulmonary complications. Furthermore, Sako et al (2017) showed that swallowing action immediately before intravenous fentanyl also reduce the incidence of FIC from 40.4% to 14.0%.…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 97%
“…Preoperative incentive spirometry has an important role in anesthesia practice, improving pulmonary function in patients with chronic obstructive and restrictive lung diseases and preventing postoperative atelectasis. Goyal et al (2017) found that preoperative incentive spirometry before giving fentanyl would suppress FIC, along with the secondary benefit of preventing postoperative pulmonary complications. Furthermore, Sako et al (2017) showed that swallowing action immediately before intravenous fentanyl also reduce the incidence of FIC from 40.4% to 14.0%.…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 97%
“…Estimated sample size was based on incidence of FIC in 32% population based on a previous study. [8] The α was taken to be 95%, the margin of error (d) was 5% and the value of P was estimated to be 32%. Total sample size was calculated as 334 so we took 112 patients in each group thus making the total sample size 336 for calculation purpose.…”
Section: Methodsmentioning
confidence: 99%
“…It is undesirable and sometimes occurs as an attack, increasing intracranial, intraocular and intra-abdominal pressures. 4 5 Intravenous lidocaine (LID) affects and reduces the intensity of post-intubation cough owing to various causes, such as the laryngoscope blade type, straining during endotracheal extubation, and smoking. After the intubation, cuff inflation will pack around the ETT and irritate the trachea.…”
Section: Introductionmentioning
confidence: 99%
“…9 10 Range of methods is available, such as local and intravenous injection of topical anesthetics to reduce cough. 5 6 11 Furthermore, intravenous use of opioids is an alternative to reducing cough at the end of the operation and during endotracheal extubation, and when the patient does not complete awakening. 2 6 However, this has frequently not been desirable.…”
Section: Introductionmentioning
confidence: 99%